The Correlation Between Social Support and Emotional Distress on Diabetes Mellitus Patients at Panembahan Senopati General Hospital Bantul - Aan Devianto; Abdul Majid; Siitni Siitni (Journal of Health (JoH), 2016)
Background: Diabetes mellitus in Bantul occupies the second position after hypertension with 10.32% prevalence among non-contagious diseases. Social support is important for diabetes mellitus patients because it influences their behavior towards reaching the desirable health status. The data obtained from 30 patients show that 15 patients received social support because no family members were there to accompany them, 5 patients suffered an emotional distress because they were anxious about their disease, and 10 patients did not have either social support problems or emotional distress. Objectives: To determine the correlation between social support and emotional distress on diabetes mellitus patients at Panembahan Senopati Hospital Bantul. Research Method: This is a correlational non experimental research which uses a cross-sectional design. The sample collection used a purposive sampling technique. The analyses technique using Kendall’s tau Results: The descriptive analysis shows that 3 respondents received low social support (10.7%), 15 respondents received medium social support (53.6%), and 10 respondents received high social support (35.7%), 8 respondents experienced low emotional distress (28.6%), and 20 respondents experienced medium emotional distress (71.4%). Conclusion: The results of Kendall’s tau correlation coefficient test show that there is a significant correlation between social support and emotional distress on diabetes mellitus patients with a p value = 0.000 and a correlation coefficient = 0.788.